Manfaat Media Pembelajaran dalam Pendidikan Islam - Khozin, Yazidul Busthomi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
attention and abilities or skills of students so that they can encourage the learning process. The benefits of learning media in Islamic education are as follows: 1. Presents learning information consistently and can be repeated or stored according to need. 2. Generate learning motivation. 3. Allow uniformity of observation and perception for student learning experiences. 4. Observing movements that are too fast. 5. Displays objects that cannot be observed with the naked eye. 6. Displaying objects that are too large. 7. Bringing objects that are difficult to obtain into the student learning environment. 8. Make abstract concepts concrete. 9. Generates more enthusiastic attention, sharpens memory, and learns quickly. 10. Helping to form habits, give birth to opinions, pay attention and think about a lesson. 11. Stimulating students to work and activating instincts of love for studying and creating a strong will to learn something. 12. Able to facilitate understanding and make lessons more lively and interesting. 13. Able to overcome difficulties and clarify difficult subject matter.